Internalizing Nationalism Awareness in Early Childhood Islamic Education Institution with The Spirit of Aswaja an-Nahdliyah - Dwi Istiyani; A.M. Wibowo (Analisa: Journal of Social Science and Religion, 2020)
This study aims at describing and analyzing the internalization of national awareness through raudlotul athfal (RA; an Islamic early childhood education institution) with the spirit of Aswaja an-Nahdliyah. Aswaja an-Nahdliyah is an ideology adopted by Nahdlatul Ulama, a major Islamic religious organization in Indonesia. This study argues that the internalization of the national awareness needs to be instilled from early age to anticipate the inﬂuence of globalization which is feared to erode the original character of a nation. Within the study, the qualitative method was adopted in order to answer two research questions: (1) how Islamic early childhood educational institutions develop nationalism awareness through the teachings of Ahlusunnah wal Jamaah; and (2) how the institutions construct the awareness of nationalism through the teachings of Ahlusunnah wal Jamaah. The results of the study show that the internalization of nationalism awareness through Islamic early childhood education institutions with the Aswaja an-Nahdliyah’s spirit has been carried out through curriculum content which has been systematically arranged in each research subject with the principle of considering early childhood characteristics. At the same time, the results of the study also show that the construction of nationalism awareness in the Islamic early childhood education institutions can be seen in Islamic holidays and national activities which were held on the Islamic early childhood institutions.